The predictive effects of classroom environment and trait emotional intelligence on Foreign Language Enjoyment and Anxiety. (February 2021) - Li, Chengchen; Huang, Jian; Li, Banban
Abstract: The field of SLA has witnessed an affective turn. It is mainly catalyzed by Positive Psychology researchers' holistic view on diverse emotions, especially positive ones, that language learners experienced. The combination of Foreign Language Enjoyment (FLE) and Anxiety (FLA) has captured the most attention. A list of learner-internal factors (e.g., trait emotional intelligence) and learner-external factors (e.g., classroom environment) have been revealed as significant predictors of the two emotions. However, few studies have sought to examine the joint effects of trait emotional intelligence and classroom environment on the two emotions. The study was thus conducted to provide a better understanding of the combined role of person-environment factors in shaping L2 emotions. Questionnaires were administered among two samples of EFL learners, namely 1718 secondary school students and 1295 university students in China. We conducted correlation and regression analyses and revealed similar patterns: 1) Trait emotional intelligence and classroom environment significantly predicted FLE and FLA separately as well as jointly; 2) FLE was more predicted by classroom environment and less by trait emotional intelligence, while FLA was more predicted by trait emotional intelligence and less by classroom environment. Our findings contribute to the emerging wave of examining the interaction between learner-internal and learner-external factors of emotions, providing important implications for L2 practitioners and researchers.